Developments and Challenges in the Caribbean Region - Cueva, Simon (Occasional Papers; Occasional Paper ;, 2000)
This paper focuses on the independent states that are full members of the Caribbean Community. It provides background information on recent developments in the Caribbean region and lays out the principal policy issues that countries will need to address in the period ahead. The Caribbean countries face several common problems and must deal with similar economic policy issues. Consequently, concentrating on the regional perspective permits a comparison of the individual responses to similar problems. The regional view throws light on the countries' movement toward convergence. The economic prospects for the region are generally satisfactory over the medium term, but the projections depend importantly on the resolve of governments to pursue appropriate policies, as well as favorable developments in the rest of the world. The relatively favorable outlook for the region is not without risks, such as a slowdown in growth in the major trading partner countries or a term of trade shock.